The Existence Of Students' Roles In Improving Religious Values For Children InLuwuk Bunter Village - Andriano, Beni; Melinda, Fitria; Yuli; Amanda, Taswah; Kurniawan, Andre; Yahya, Muhammad Ighfar Dwi; Lavenia Regita Desyanti; Rahmi, Sofianatur (Amala Jurnal Pengabdian Kepada Masyarakat, 2025)
ThThe community service program through the Student Community Service (KKN) in Luwuk Bunter Village, Cempaga District, East Kotawaringin Regency, focused on enhancing religious values among children. The main issue faced by the community was the lack of religious activities for children, such as Qur’an recitation and congregational prayers, due to limited teaching resources. The KKN team applied a participatory approach by involving children, community leaders, and mosque administrators in various religious activities. The methods included regular congregational worship, Qur’an literacy guidance, and mentoring in daily manners and ethics. The results of the program showed an increase in children’s participation in religious activities that were previously inactive, as well as the revitalization of the mosque’s role as a center for religious education. This program had a positive impact by fostering religious habits, motivating children to learn, and raising community awareness of the importance of instilling religious values from an early age.